The growth of tulip tissues in vitro - Wright, Neal Anthony (1981)
Large numbers of adventitious shoots have been induced to form in vitro on floral stem sections of Tulipa gesneriana L. cultivar Merry Widow. In comparison with explants of scale and axillary bud, floral stem tissues showed the greatest potential for shoot production. A modified Murashige & Skoog medium contained inorganic salts and vitamins at full strength and supplemented with benzylamino-purine and napthalene-acetic acid at 1 mg‾1 induced shoots on 70%-90% of floral stem explants.